Current PI-funnel control with anti-windup for synchronous machines - Hackl, C. M. (2015 54th IEEE Conference on Decision and Control (CDC), 2015)
We discuss current funnel control for synchronous machines (SMs) which assures current reference tracking with prescribed transient accuracy without the knowledge of system parameters and the (nonlinear) flux linkage. We present a generic (nonlinear) model of SMs and a simplified actuator model of the voltage source inverter. The dynamics describe a two-input two-output system with positive definite high-frequency gain, (strict) relative degree one and bounded-input bounded-output (BIBO) stable zero-dynamics subject to actuator (input) saturation. To facilitate steady state accuracy (for constant references and disturbances) and in view of the saturated control action, the funnel controller is combined with a proportional-integral (PI) controller (i.e., PI-funnel control) with anti-windup. Comparative simulation results illustrate the control performance of funnel control, PI-funnel control and PI-funnel control with anti-windup.